Activation of a Metal‐Halogen Bond by Halogen Bonding - Wolf, Julian (John Wiley and Sons Inc., 2020)

(untitled) (Angew Chem Int Ed Engl)
In recent years, the non‐covalent interaction of halogen bonding (XB) has found increasing application in organocatalysis. However, reports of the activation of metal‐ligand bonds by XB have so far been limited to a few reactions with elemental iodine or bromine. Herein, we present the activation of metal‐halogen bonds by two classes of inert halogen bond donors and the use of the resulting activated complexes in homogenous gold catalysis. The only recently explored class of iodolium derivatives were shown to be effective activators in two test reactions and their activity could be modulated by blocking of the Lewis acidic sites. Bis(benzimidazolium)‐based halogen bonding activators provided even more rapid conversion, while the non‐iodinated reference compound showed little activity. The role of halogen bonding in the activation of metal‐halogen bonds was further investigated by NMR experiments and DFT calculations, which support the mode of activation occurring via halogen bonding.